Saurischian-dominated tracksites and first Cretaceous lizard trackway from China from the Hekou Group (Lower Cretaceous) of Lanzhou-Minhe Basin, Gansu, Northwest China. (2nd December 2021) - Xing, Lida; Li, Daqing; Lockley, Martin G.; Persons, W. Scott; Klein, Hendrik; Yang, Jingtao; Li, Longfeng; Peng, Cuo
ABSTRACT: A total of 31 Lower Cretaceous tetrapod tracksites have been reported from four areas in Gansu Province, China: Yanguoshia, Guanshan, Zhongpu and Honggu. Here we report on the previously undescribed track types found at seven of these sites, five of which are sauropod dominated, with one site yielding ornithopod tracks and another one yielding theropod tracks. The Tianjiawan site is of particular significance for having produced the first lizard trackway from the Cretaceous of China and only the fourth global occurrence from this time period. The lizard trackway is tentatively assigned to ? Neosauroides ichnosp. indet., and compared with Neosauroides from the Cretaceous of Korea. As in Korea the Gansu lizard trackway occurs in lake margin sediments suitable for the preservation of the tracks of small tetrapods.